Analisis Faktor-Faktor yang Mempengaruhi Harga Saham pada Perusahaan yang Terdaftar di Jakarta Islamic Index - Sari, Ricka Wulan; Setiawan, Iwan; Barnas, Benny; Tripuspitorini, Fifi Afiyanti (Journal of Applied Islamic Economics and Finance, 2023)
The title of this research is "Analysis of Factors Affecting Stock Prices in Companies Listed on the Jakarta Islamic Index". The aim is to clarify the circumstances that affect stock prices in issuers listed on the JII during the 2017-2021 period consisting of Return on Asset, Earning per Share, Debt to Asset Ratio, Gross Domestic Product, Inflation, and BI Rate. The sample in the study consisted of 14 issuers. The data analysis technique uses panel data regression analysis using the Eviews tool. The results of the study showed that ROA, and EPS had a significant impact with a positive direction on stock prices, on the other hand DAR, GDP, Inflation, BI Rate had no impact. Meanwhile, simultaneously all independent variables have an impact on the dependent variable.